The Effect of Naturalistic Developmental Behavioral in Improving Vocabulary Skills in Children with Developmental Language Disorder in Depok City - Nuthia Fadlina; Kiyat Sudrajat; Anggi Resina Putri (Jurnal EduHealth, 2025)
Background: Naturalistic Developmental Behavioral Intervention (NDBI) is a type of intervention used to teach vocabulary and test cross-modality generalization between expressive and receptive modalities. Developmental Language Disorder (DLD) is a disorder characterized by persistent difficulties in the acquisition, comprehension, production, or use of language, both spoken and signed. NDBI can be used to teach vocabulary to children with DLD. Purpose: This study aims to determine whether NDBI has an effect on increasing the vocabulary of children with DLD in Depok City. Method: This study used quantitative research. The research design used in this study was experimental research with a one-group pretest-posttest design. The sampling technique used in this study was purposive sampling. The sample in this study consisted of 10 children with DLD in Depok City. The data were analyzed descriptively and bivariately. The statistical test used was the Paired t-test because the data were normally distributed. Results: The results of the statistical test, namely the paired t-test, showed that the effect of NDBI in increasing the vocabulary of children with DLD had p-value is 0.13, so p-value is <0.05, then Ho was rejected and Ha was accepted. Conclusion: This study found that there was a significant effect of the use of naturalistic developmental behavior on increasing the vocabulary of children with DLD in Depok City.